Business Model Objectives' Effects On Marketing Innovation Initiatives: A Comparative Analysis Of Manufacturing And Service Companies - Zainul Wasik; Muchammad Saifuddin; Imelda Sitinjak; C. Candraningrat Candraningrat (Journal of Managerial Sciences and Studies, 2024)
This research aims to examine the distinctions and overlaps that exist between manufacturing and service companies concerning how business model goals affect marketing innovation initiatives. The goals of business models and marketing innovation initiatives are the main topics of this study. According to the Oslo Manual, innovations in marketing entail adjustments to pricing, location, promotion, and product design. The study examines the connections between marketing innovations and business model objectives by analyzing data from 3,240 organizations, of which 1,986 are service providers and 1,254 are manufacturers. The implementation of marketing innovation yields different outcomes based on the goals of the business model and the types of businesses (manufacturing or service) that are taken into consideration. By pinpointing the specific distinctions between the service and manufacturing industries more precisely than previous research, this study goes beyond previous research. The size and age of the company do not significantly limit the introduction of fresh approaches to marketing in the production or service industries. On the other hand, most of the time, marketing innovations are motivated primarily by the intention of the company concept to enter a new market. It's innovative to concentrate on business impact of model objectives on marketing innovations.